Fairy Tale Therapy Within the Speech Development System of Preschool-age Children - Matsyuk, Zoriana; Fenko, Maria (East European Journal of Psycholinguistics, 2016)
The issue of developing professionalism in teachers is acquiring particular importance because of the fact that difficult social conditions are leading to an expanding range of problems that require solutions at the pedagogical level. Fairy tale therapy is an effective method used to exert a direct influence on the emotional and sensory spheres of the personality to change behaviour patterns and provide an analysis of children’ innate abilities. In this article the theoretical principles of the use of fairytale therapy in psycho-pedagogical practice are substantiated. In particular the criteria and the performance indicators of speech development of preschool-age children were determined in situations where they engaged in fairytale-related play: 1) the level of fairy tale-based learning; the ability to recount familiar fairytales; the ability to evaluate their own narration and that of a friend; 2) children's self-sufficiency in making up plots involving fairy tale-based situations; the originality of the fictitious fairy tale plot; and the presence of tools for creative self-expression. Particular emphasis is put on the children’s creative self-expression in speech, to which the use of fairy tale therapy contributes directly: children are immersed in the fairy-tale world, which extends the maximum speech activity of the children in the educational/developmental setting of their school;  the presence of positive emotional stimuli in formulating creative narratives; the devising of successful scenarios in activities involving a combination of speech and play-acting; providing incentives for oral self-expression and creative initiative in preschool-age children in fairy tale-related situations. The results of the research which was conducted demonstrate that the use of the fairy tale-therapy method is appropriate and justified.ReferencesАлексеенко В. В. Играем в сказку. Воспитание и развитие личности ребенка 2–7 лет. – М.: РИПОЛ.Aleksеіenko, V.V. (2008). Igraem v skazku. Vospitanie i razvitie lichnosti rebionka 2–7 let. [Playing Fairy-Tale. Educating and Developing Personality from 2 -7]. Moscow: RYPOL.Бурчик О. В. Групова казкотерапія в особистісно-орієнтованому вихованні дітей // Высник Житомирського державного ун-ту ім. Івана Франка. – 2005, № 25. – С. 203-205.Bourchyk, O.V. (2005). Grupova kazkoterapia v osobystisno-orientovanomu vyhovanni ditej [Group Fairy-Tale Therapy in Personality-oriented Education of Children]. Visnyk Zhytomyrskoho derzhavnoho universytetu imeni I. Franka, 25, 203-205.Давыдова Т. Т. Сказка // Лит. Учеба. – 2003., № 1.Davуdova, T. T. (2003). Skazka [Сказка]. Lyt. Ucheba, 1.Деркач О. О. Педагогіка творчості: Арт-терапія та казкотерапія на допомогу вчителю, вихователю, праткичному психологу. Вінниця, 2003.Derkach, O. O. (2009). Pedahohika tvorchosti: Art-terapiia ta kazkoterapiia na dopomohu vchyteliu, vykhovateliu, praktychnomu psykholohu]. Vinnytsia.Кирилюк О. С. Універсалії культури і семіотика дискурсу : казка та обряд. – Одеса: ЦГО НАНУ, 2003. Kyryliuk, O. S. (2003). Universalii kultury i semiotyka dyskursu: kazka ta obriad [The Cultural Universals and Semiotics of Discourse: Fairy-Tale and Rite]. Odesa: TsHO NANU.Мелетинский Е. М. От мифа к литературе. – М.: РГГУ, 2000.Meletynskyij, E. M. (2000). Ot Mifa k Literature [From Myth to Literature]. Moscow: RGGU.Нассруллаева Н. Н. Влияние содержания и языковых средств народной сказки на образность и выразительность речи старшего дошкольника. – К.: Рад. школа, 1982.Nassrullaeva, N. N. (1982). Vlyianie soderzhansiia i yazykovykh sredstv narodnoij skazki na obraznost i vyraziytielnost rechy starsheho doshkolnyka [The Impact of Content and Linguistic Means of Folk-Tale on the Imagery and Expressiveness of Older Pre-schooler Speech]. Kyiv: Rad. Shkola.Померанцева Э. В. Русское народное поэтическое творчество. – М.: Учпедгиз, 1956.Pomerantseva, Е. V. (1956). Russkoe narodnoe Poetiycheskoe Tvorchestvo [Russian Folk Poetic Art]. Moscow: Uchpedgiz.Пропп В. Морфология волшебной сказки. Исторические корни волшебной сказки. – М.: АСТ, 1998.Propp, V. (1998). Morfolohyia volshebnoij skazki. Istoricheskie korny volshebnoij skazki [The Morphology of Fairy-Tale]. Moscow: AST.Соколов Д. Сказки и сказкотерапия. –М.: Экcмо-Пресс, 2001.Sokolov, D. (2001). Skazki i skazkoterapiia [Fairy-Tales and Fairy-Tale Therapy]: Moscow: Eksmo-Press.Вачков Я. Сказкотерапия: Развитие самосознания через психологическую сказку. –М.: Ос-89. – С. 144.Vachkov, Y. V. (2001). Skazkoterapiia: Razvitie samosoznanyia cherez psykholohycheskiju skazku [Fairy-Tale Therapy]. Moscow: Os-89.Великий тлумачний словник сучасної української мови/ Укл. і гол. ред. В. Т. Бусел. – К.; Ірпінь: Перун, 2004.Velykyj tlumachnyj slovnyk suchasnoi ukrainskoi movy (2004). V. Busel, Ed. [Great Explanatory Dictionary of Modern Ukarinain]. Kyiv; Irpin: Perun.Якименко С. І. Формування основ світогляду у дітей молодшого шкільного віку засобами казки: теорія і практика. – Київ: Знання, 1999.Yakymenko, S. I. (1999). Formuvannia osnov svitohliadu u ditej molodshoho shkilnoho viku zasobamy kazky: teoriia i praktyka [Формування основ світогляду у дітей молодшого шкільного віку засобами казки: теорія і практика]. Kyiv: Znannia.Зинкевич-Евстигнеева Т. Формы и методы работы со сказками. – СПб: Речь, 2006.Zynkevych-Evstyhneeva, T. D. (2006). Formy i metodu raboty so skazkami [Forms and Methods of Working with Fairy-Tales]. S.-Petersburg: Rech.